Double rare ABO blood group inheritance - Nandy, CK; Begum, Shahida; Uddin, SM Jalal; Sengupta, Ashim Kumar; Biswas, Joly; Khatun, Ayesha (KYAMC Journal, 2013)
Blood group system ABO phenotype Oh Bombay detected while cross-matching with different donors and by the by, family screening leads to a unusual matting result when mother AB and father O. DOI: http://dx.doi.org/10.3329/kyamcj.v1i2.13321 KYAMC Journal Vol.1(2) January 2011, 84-86